The role of social support on vocational school students’ career choices - Suyitno Suyitno; Dwi Jatmoko; Aci Primartadi; Dianna Ratnawati; Haris Abizar (Institute of Advanced Engineering and Science, 2024)
Strengthening career choices for vocational students is essential in preparing them to enter the world of work. Many studies highlighted the importance of career choices that are by the areas of expertise for vocational students and even examine the mechanism for strengthening their career choices. However, limited studies still focused on testing models for forming career choices by involving social support, career self-efficacy, and vocational identity in an integrative manner. Therefore, this study investigated the model of developing student career choices by applying for social support, career self-efficacy, and vocational identity. This study used structural equation modelling (SEM) analysis with Amos 18 software. The study results revealed that social support, career self-efficacy, and vocational identity factors directly influence vocational students’ career choices. In addition, career self-efficacy mediates the effect of social support on career choice. Finally, vocational identity moderates the interaction of the independent variables (social support and career self-efficacy) and the dependent variable (career choice). The results of this study provided important implications for lecturers to implement learning strategies that aim to strengthen vocational students’ career choices.